2018
DOI: 10.1126/scisignal.aai7838
|View full text |Cite
|
Sign up to set email alerts
|

Jak-TGFβ cross-talk links transient adipose tissue inflammation to beige adipogenesis

Abstract: The transient activation of inflammatory networks is required for adipose tissue remodeling including the "browning" of white fat in response to stimuli such as 3-adrenergic receptor activation. In this process, white adipose tissue acquires thermogenic characteristics through the recruitment of so-called beige adipocytes. We investigated the downstream signaling pathways impinging on adipocyte progenitors that promote de novo formation of adipocytes. We showed that the Jak family of kinases controlled TGF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…It has also been shown that AT development and remodeling are critically dependent on inflammatory signaling early in postnatal life (85). Most recently, β 3 adrenergic stimulation of lipolysis has been shown to trigger IL-6/JAK/STAT3 signaling and promote beige adipocyte development (36). Our findings on the role of AKG/ PAF/IL-6/STAT3 signaling in BeAT development are in line with these recent findings and confirm that BeAT development in the infant requires transient inflammatory signaling (86).…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…It has also been shown that AT development and remodeling are critically dependent on inflammatory signaling early in postnatal life (85). Most recently, β 3 adrenergic stimulation of lipolysis has been shown to trigger IL-6/JAK/STAT3 signaling and promote beige adipocyte development (36). Our findings on the role of AKG/ PAF/IL-6/STAT3 signaling in BeAT development are in line with these recent findings and confirm that BeAT development in the infant requires transient inflammatory signaling (86).…”
Section: Methodssupporting
confidence: 89%
“…MitoTracker Green and Red staining of mitochondria confirmed that they were functional (Figure 3 Figure 3E). The level of NADH-DH activity reflects mitochondrial respiration (35), which is increased in beige adipocytes (36). In the presence of ATMs, AKG treatment increased Ucp1 transcription in 3T3-L1 adipocytes ( Figure 3F).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Expression of constitutively active STAT3 (C-STAT3) has been shown to restore BAT differentiation of Tyk2−/− preadipocytes and reverse the obese phenotype in Tyk2−/− mice [155]. A recent report showed that transient activation of the JAK family of kinases and STAT3 signaling in the context of β-adrenergic tissue remodeling increased the potential for thermogenic adipocyte differentiation i.e., browning [156]. Although these data suggest that there is a role for STAT3 in adipose tissue browning, the authors also point-out that this is only in the case of transient inflammation but not chronic inflammation.…”
Section: Stat3 and Cachexiamentioning
confidence: 99%
“…Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway plays an important role in a variety of physiologic processes including development, hematopoiesis, inflammation, and lipid metabolism progress (10)(11)(12)(13)(14). The JAK family of receptor-associated tyrosine kinases act as primary transducers of multiple cytokine receptors and mediate a variety of their effects through the phosphorylation of the transcription factor STATs (12,(15)(16)(17)(18)(19). JAK/STAT pathway also participates in adipocyte differentiation (14), and of the 7 known STATs, only STAT3 and STAT5 have been reported to positively affect adipogenesis (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%